2021
DOI: 10.3389/fonc.2021.655906
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Plexus Block Versus Periprostatic Nerve Block for Ultrasound-Guided Prostate Biopsy: A Meta-Analysis

Abstract: BackgroundTo relieve prostate biopsy-related pain, various local anesthetic methods have been used. The best approach was periprostatic nerve block (PNB) in the past decade. Recently, pelvic plexus block (PPB) was employed to ultrasound-guided prostate biopsy. Compared with the PNB, the PPB may block a more extensive area. Therefore, PPB may be more effective in relieving prostate biopsy-related pain. However, several prospective randomized controlled trials (RCTs) comparing PPB and PNB drew conflicting conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…With the incidence rate of prostate cancer(PCa) increasing, the number of prostate biopsies(PBx) were increasing every year, PBx was the most important method for diagnosing PCa [1][2][3]. The disadvantage of TPBx was poor pain control, and most of the pain in the prostate biopsy was derived from the prostate capsule [4].How to block the pain of the structure between the skin and the prostate capsule was the key to relieve the pain of TPBx.Nash et alFirst reported in 1996 that anesthetics were injected into the area between the prostate and seminal vesicle, which could directly penetrate the neurovascular bundle and reduce the pain associated with TRUS guided prostate biopsy [5].PNB was the best anesthesia for prostate biopsy in the past decade [6][7][8][9].Further studies showed that PNB combined with perineal subcutaneous anesthesia and intra rectal lidocaine gel was a safer and more effective method for PBx local anesthesia,it could almost replace the total intravenous anesthesia [10,11]. However, the anesthetic effect of some patients receiving PNB was still poor, especially some patients with large prostate volume still could not stand the pain during biopsy [12].…”
Section: Introductionmentioning
confidence: 99%
“…With the incidence rate of prostate cancer(PCa) increasing, the number of prostate biopsies(PBx) were increasing every year, PBx was the most important method for diagnosing PCa [1][2][3]. The disadvantage of TPBx was poor pain control, and most of the pain in the prostate biopsy was derived from the prostate capsule [4].How to block the pain of the structure between the skin and the prostate capsule was the key to relieve the pain of TPBx.Nash et alFirst reported in 1996 that anesthetics were injected into the area between the prostate and seminal vesicle, which could directly penetrate the neurovascular bundle and reduce the pain associated with TRUS guided prostate biopsy [5].PNB was the best anesthesia for prostate biopsy in the past decade [6][7][8][9].Further studies showed that PNB combined with perineal subcutaneous anesthesia and intra rectal lidocaine gel was a safer and more effective method for PBx local anesthesia,it could almost replace the total intravenous anesthesia [10,11]. However, the anesthetic effect of some patients receiving PNB was still poor, especially some patients with large prostate volume still could not stand the pain during biopsy [12].…”
Section: Introductionmentioning
confidence: 99%